The toll of epidemic diseases in the Płock Governorate between 1864 and 1914 - Milewska, Marta (Requiem, 2025)
Epidemic diseases were a serious problem of medical care in the Płock Governorate in the years 1864–1914. The main infectious diseases occurring in the above-mentioned province were cholera, smallpox, scarlet fever, typhus, typhus, croup, measles, whooping cough, measles and tuberculosis. Analyzing the incidence of the above-mentioned diseases, it can be concluded that the Płock Governorate was a mosaic of diseases that occurred with greater or lesser severity. However, the aim of the article is to draw attention to the mortality resulting from these diseases. Each of the above epidemic diseases took its toll. It took many lives. The article also draws attention to the problems of medical care in the Płock Governorate in the fight against selected epidemic diseases, namely cholera, smallpox and scarlet fever.